Pengembangan Prototipe Media Pembelajaran pada Alat Peraga â€œMobil Bertenaga Anginâ€ - Anisa Kartika Wicaksiwi; Feby Deatri Mayangsari (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2022)
Experiential learning media initiatives in junior high school because students will more easily understand concepts through experimental activities compared to just listening to information from the teacher. The method used is a survey of students' interests and motivations after trying the media props "wind powered car." The number of participants surveyed was seven junior high school students. The small amount is intended to obtain initial data about interest and motivation in the learning media. The survey results show that the majority of students are interested in the media or have high interest and motivation in experiential learning media. Based on the survey results, the prototype of the learning media that has been made is good enough, so it can be used in larger classes. Keywords: culture, experiential learning, learning media.